1998
DOI: 10.1126/science.281.5385.2042
|View full text |Cite
|
Sign up to set email alerts
|

Protein Kinase C Isotypes Controlled by Phosphoinositide 3-Kinase Through the Protein Kinase PDK1

Abstract: Phosphorylation sites in members of the protein kinase A (PKA), PKG, and PKC kinase subfamily are conserved. Thus, the PKB kinase PDK1 may be responsible for the phosphorylation of PKC isotypes. PDK1 phosphorylated the activation loop sites of PKCzeta and PKCdelta in vitro and in a phosphoinositide 3-kinase (PI 3-kinase)-dependent manner in vivo in human embryonic kidney (293) cells. All members of the PKC family tested formed complexes with PDK1. PDK1-dependent phosphorylation of PKCdelta in vitro was stimula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

40
887
7
2

Year Published

1999
1999
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 1,023 publications
(936 citation statements)
references
References 17 publications
40
887
7
2
Order By: Relevance
“…Akt, in turn, inhibits Forkhead transcription factors, responsible for inducing expression of death genes; phosphorylates and therefore inhibits glycogen synthase kinase-3b activity, involved in neuronal apoptosis (Patapoutian and Reichardt, 2001); induces expression of survival genes, such as Bcl-2 and Bcl-x L , by activating cyclicAMP response element binding protein and nuclear factor-kB (Downward, 2004); phosphorylates and deactivates proapoptotic Bad (Datta et al, 2000) and caspase-9 (Zhou et al, 2000); and blocks proapoptotic action of the p75 neurotrophin receptor ). Interestingly, activation of PDK-1 leads to phosphorylation and activation of protein kinase C (PKC) family members (Chou et al, 1998;Le Good et al, 1998), and PI-3,4,5-P 3 in response to growth factor activation enhances phospholipase C (PLC)g activity (Falasca et al, 1998). It is pertinent to mention that we have found altered activation of PKC in postmortem brain of suicide subjects (Pandey et al, 2004) and that PLC g may have an important role in depressive behavior (Dwivedi et al, 2005b).…”
Section: Discussionmentioning
confidence: 91%
“…Akt, in turn, inhibits Forkhead transcription factors, responsible for inducing expression of death genes; phosphorylates and therefore inhibits glycogen synthase kinase-3b activity, involved in neuronal apoptosis (Patapoutian and Reichardt, 2001); induces expression of survival genes, such as Bcl-2 and Bcl-x L , by activating cyclicAMP response element binding protein and nuclear factor-kB (Downward, 2004); phosphorylates and deactivates proapoptotic Bad (Datta et al, 2000) and caspase-9 (Zhou et al, 2000); and blocks proapoptotic action of the p75 neurotrophin receptor ). Interestingly, activation of PDK-1 leads to phosphorylation and activation of protein kinase C (PKC) family members (Chou et al, 1998;Le Good et al, 1998), and PI-3,4,5-P 3 in response to growth factor activation enhances phospholipase C (PLC)g activity (Falasca et al, 1998). It is pertinent to mention that we have found altered activation of PKC in postmortem brain of suicide subjects (Pandey et al, 2004) and that PLC g may have an important role in depressive behavior (Dwivedi et al, 2005b).…”
Section: Discussionmentioning
confidence: 91%
“…This dual phosphorylation reaction results in full activation of protein kinase B [142]. Of interest, PDK1 can also phosphorylate and activate PKCf and -d and p70 S6k , indicating the possibility of a number of interlinked signalling pathways [143]. A recent report has demonstrated that protein kinase B is activated in airway smooth muscle by the mitogens PDGF and a-thrombin in a PI3K-dependent manner, and this effector presumably lies upstream of p70 S6k on the pathway which appears to drive cellular proliferation ( fig.…”
Section: Activation Of Phosphoinositide 3-kinasementioning
confidence: 99%
“…Among them, 3-phosphoinositide-dependent protein kinase-1 (PDK-1) was identified to be an immediate downstream mediator of PI3-K and was activated upon phosphorylation on residue Ser-241 (Casamayor et al, 1999). Activated PDK-1 controls cell proliferation, survival, nutrients uptake and storage, by further activating its downstream AGC (cAMP-dependent, cGMPdependent, protein kinase C) family of protein kinases including AKT (Alessi et al, 1997;Wick et al, 2000b), protein-kinase C (PKC) (Le Good et al, 1998;Balendran et al, 2000), serum-and glucocorticoidinduced kinase (SGK) (Mora et al, 2004), and ribosomal p70S6 kinase (Pullen et al, 1998). Hence, PDK-1 functions as a pivotal signalling molecule at the apex of complex networks of intracellular signalling (Toker and Newton, 2000;Storz and Toker, 2002).…”
mentioning
confidence: 99%